Computer-Mediated Communication and Majority Influence: Assessing the Impact in an Individualistic and a Collectivistic Culture - Tan, Bernard C. Y.; Wei, Kwok-Kee; Watson, Richard T.; Clapper, Danial L.; McLean, Ephraim R. (Management Science, 1998)
Strong majority influence can potentially harm organizational decisions by causing decision makers to engage in groupthink. This study examines whether and how computer-mediated communication (CMC) can reduce majority influence and thereby enhance the quality of decisions in some situations. To measure the impact of CMC on majority influence, three settings (unsupported, face-to-face CMC, and dispersed CMC) were compared. Matching laboratory experiments were carried out in an individualistic (the US) and a collectivistic culture (Singapore) to determine how the impact of CMC might be moderated by national culture. An intellective and a preference task were used to see whether the impact of CMC might be moderated by task type. The results showed that the impact of CMC on majority influence was contingent upon national culture. In the individualistic culture, majority influence was stronger in the unsupported setting than the face-to-face CMC and dispersed CMC settings. In the collectivistic culture, there were no corresponding differences. The results also revealed that the impact of CMC on majority influence was not moderated by task type. Instead, task type had a direct impact on majority influence. Regardless of the setting involved, majority influence was stronger with the preference than the intellective task. Besides demonstrating how cultural factors may moderate the impact of CMC, this study raises the broader issue of cultural relativism in current knowledge on CMC.